Consumers’ Vulnerability and E-commerce purchase behavior: A serial mediation model - Thu Thuy Nguyen; Hong Tam Nguyen; Anh Vu Nguyen; Phuong Thao Tran; Hong Nhung Mai; Thi Van Anh Pham (Telematics and Informatics Reports)
The current study investigates the influence of consumers’ vulnerability on E-commerce purchase behavior, and how Uncertainty and Perceived behavioral control can affect these relationships. While contemporary studies have investigated the effects of consumers’ vulnerability on e-commerce purchase intentions with mixed results, the research formulates a model that explains specifically how two dimensions of consumers’ vulnerability (lack of skills, lack of knowledge), perceived behavioral control, and uncertainty intricately affect each other in determining customers’ e-commerce purchase behavior. The quantitative study uses data from a questionnaire survey with 364 valid responses. Structural equation modeling (SEM) with 5000 bootstrapping replications was employed to test formulated hypotheses. The results indicate that consumers’ vulnerability of capability negatively impacts customers’ perceived behavioral control and positively affects the perceived Uncertainty of E-commerce. In addition, Consumers’ Uncertainty and Perceived behavioral control serve as serial mediators in the relationship between consumers’ vulnerability and e-commerce purchase behavior. These findings offer some new theoretical and practical implications and insights into consumer decision-making under vulnerability and provide actionable guidance for designing more inclusive and trustworthy e-commerce environments.